Immunomodulator effect of topical zinc oxide application in tuberculin skin test - Nuhoglu, Cagatay (North Clin Istanb, 2018)
OBJECTIVE: We aimed to evaluate the sensitivity of tuberculin skintest (purified protein derivative-PPD) by topical zinc application on test site to improve diagnostic reliability. METHODS: We performed this study in 100 children aged 6–14 years, and plasma zinc levels were analyzed after 10–12 hours fasting. After PPD, we applied 40% zinc oxide cream on one forearm and placebo on the other forearm. PPD indurations were measured 72 hours later. RESULTS: In this study, 26% of the children showed increases in PPD induration following local zinc applications. There was no correlation between indurations size and serum zinc levels. CONCLUSION: We concluded that topical zinc cream application can enhance sensitivity of tuberculin reactivityin the diagnosis of tuberculosis.